CORPORATE NETWORK SECURITY USING EXTENDED ACCESS CONTROL LIST (ACL) IN A SIMULATION ENVIRONMENT (FUDMA JOURNAL OF SCIENCES, 2023)
Routers (sometimes gateways) are important devices in internetworks. Routers play the task of interconnecting and partly securing network devices by forwarding packets from source address to destination address. Security on routers is achieved by determining whether packets to be forwarded are authorized to get to their desired destination. This action can be carried out by exploiting misconfigured ACL (Access Control List). ACL is a list of rules that determine whether and how to forward or discard a packet on a network i.e. it filters packets. ACL can also be used for implementing network policies such as NAT (Network address Translation). A correct ACL configured on a router examines each packet to determine whether to forward or drop the packet, this decision is based on the rules specified within the access lists leading to secure network and packet flow. In corporate organizations sometimes there is an interconnection between various LANs but not all devices are allowed to access a device on particular LAN because of the nature of the resources on that device, hence in such scenario ACL is a good choice when looking for the appropriate tool to control the device access. In this paper we have designed a model of a corporate network with 3 Local Area Networks (LANs), and packets traverse the devices on the LANs). After applying the correct ACL configurations on the LAN 2 Router access is restricted on LAN 2 server, which now only receives packets from an authorized device, this greatly enhances the security
Keywords: Ping of Death, Zombie, DoS, DDoS, Smurf Attack